A Synthetic Biology Approach Identifies the Mammalian UPR RNA Ligase RtcB - Lu, Yanyan; Liang, Feng-Xia; Wang, Xiaozhong (Molecular cell, 2014)
Signaling in the ancestral branch of the unfolded protein response (UPR) is initiated by unconventional splicing of HAC1/XBP1 mRNA during endoplasmic reticulum (ER) stress. In mammals, IRE1α has been known to cleave the XBP1 intron. However, the enzyme responsible for ligation of two XBP1 exons remains unknown. Using an XBP1 splicing-based synthetic circuit, we identify RtcB as the primary UPR RNA ligase. In RtcB knockout cells, XBP1 mRNA splicing is defective during ER stress. Genetic rescue and in vitro splicing show that the RNA ligase activity of RtcB is directly required for the splicing of XBP1 mRNA. Taken together, these data demonstrate that RtcB is the long-sought RNA ligase that catalyzes unconventional RNA splicing during the mammalian UPR. [Display omitted] •A synthetic apoptosis circuit enables the identification of a UPR RNA ligase•RtcB catalyzes unconventional XBP1 mRNA splicing during ER stress•A subset of RtcB is associated with the endoplasmic reticulum•IRE1α and RtcB reconstitute XBP1 splicing in vitro Mammalian XBP1 mRNA undergoes unconventional splicing during ER stress as part of the unfolded protein response (UPR). Using a synthetic genetic circuit, Lu et al. identify RtcB as the UPR RNA ligase that catalyzes XBP1 splicing.